Evaluation of Some Antioxidants and Oxidative Stress Tests in Iraqi Lung Cancer Patients - Israa F. Ascar; Fayhaa M. Khaleel; Areej Sh. Hameed; Musaab Kadhim Alabboodi (Baghdad Science Journal, 2022)
Vitamin K-dependent protein (VKDP) contributes to the development of lung cancer. The purpose of this research was to better understanding of the role of blood matrix Gla protein (MGP), VKDPs, Malondialdehyde (MDA), Superoxide dismutase (SOD) and Vitamin K (Vit K) in Iraqi patients with lung cancer before and after the first cycle of chemotherapy. Blood samples were collected from Al amal National Hospital for cancer treatment from October 2021 to May 2022, and a total of 80 samples were collected, divided into two groups (40 patient before taking a chemotherapy and 40 patients after taking chemotherapy), ranging in age from 20 to 45 years old. The results showed that although there were highly statistically significant differences in MDA, VKDPS, SOD, and Vit K, there was no difference in MGP serum levels between the two groups (P = 0.05). The current study found a significant positive correlation between MGP and VK1 values.Correlations before and after treatment. Based on the results obtained, no role for the blood matrix protein Gla was observed in patients after and before treatment. Therefore, it cannot be considered a sign of patients' response to treatment. In addition, it was observed that lung cancer patients had lower levels of SOD enzyme, which indicates the effect of treatment on the disease, in which knowing the extent to which the body is responding or not responding to treatment.